Benefit as a Standard Unit of Measure for Arts Organizations: A Conceptual Analysis - DeVereaux, Constance; Keeney, Kate (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2023)
Benefit is a commonly used concept for expressing positive outcomes of arts participation. The inherent ambiguity of benefit applied to a broad range of arts activities raises issues for research, decision-making, program design, and evaluation. This article offers a conceptual analysis of benefit as a standard unit of measure for design and evaluation of third sector arts organization services. In this article, we explore the possibilities for a standard unit of measure, called Benefit Unit that works toward dispelling the inherent ambiguities of “benefit” in the current discourse on arts programs and services. Conceptual analysis is applied to existing theories of benefit analysis and transaction theory, to advance a framework for Benefit Unit that offers ease of use, coherence, and wide acceptance. Developed for arts organizations, we see potential for any nonprofit organization seeking to establish appropriate measures of the intangible merits of its services. Our research is aimed at decision makers, policy agents, public administrators, and funders who have interest in improving available tools for measuring outcomes of arts services.